Blockchain /? - Laurence, Tiana (For dummies)
Blockchain is the techno-magic that enables cryptocurrencies and impacts the worlds of finance, insurance, supply chain management, and others. But you don't need to be a programmer or financial wizard to understand blockchain; you just need this book!